2024
DOI: 10.1093/mnras/stae1430
|View full text |Cite
|
Sign up to set email alerts
|

Gas assisted binary black hole formation in AGN discs

Henry Whitehead,
Connar Rowan,
Tjarda Boekholt
et al.

Abstract: We investigate close encounters by stellar mass black holes (BHs) in the gaseous discs of active galactic nuclei (AGNs) as a potential formation channel of binary black holes (BBHs). We perform a series of 2D isothermal viscous hydrodynamical simulations within a shearing box prescription using the Eulerian grid code Athena++. We co-evolve the embedded BHs with the gas keeping track of the energetic dissipation and torquing of the BBH by gas gravitation and inertial forces. To probe the dependence of capture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…The presence of gas around the merger may facilitate electromagnetic counterparts to these events (e.g., McKernan et al 2019;Tagawa et al 2023). The BBHs may be captured in the AGN disks from the nuclear star cluster (Bartos et al 2017), or form in situ via migration (e.g., Bellovary et al 2016;Secunda et al 2019;McKernan et al 2020b) or gas-assisted kinetic energy dissipation (Tagawa et al 2020;Rowan et al 2023Rowan et al , 2024Whitehead et al 2024). Regarding the latter, recently found that BBHs commonly form with large initial eccentricities and retrograde orbits, which was largely confirmed by Whitehead et al (2024).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The presence of gas around the merger may facilitate electromagnetic counterparts to these events (e.g., McKernan et al 2019;Tagawa et al 2023). The BBHs may be captured in the AGN disks from the nuclear star cluster (Bartos et al 2017), or form in situ via migration (e.g., Bellovary et al 2016;Secunda et al 2019;McKernan et al 2020b) or gas-assisted kinetic energy dissipation (Tagawa et al 2020;Rowan et al 2023Rowan et al , 2024Whitehead et al 2024). Regarding the latter, recently found that BBHs commonly form with large initial eccentricities and retrograde orbits, which was largely confirmed by Whitehead et al (2024).…”
Section: Introductionmentioning
confidence: 89%
“…We used the publicly available code Athena++ (Stone et al 2020) with the shearing box approximation (Hawley et al 1995;Stone et al 1996) and coupled it with the N-body code REBOUND (Rein & Liu 2012). With this, we accurately evolve arbitrary configurations of the three-body system without relying on ad hoc precession terms (e.g., or simplifying assumptions (e.g., Paper I; Whitehead et al 2024).…”
Section: Numericsmentioning
confidence: 99%
See 2 more Smart Citations